2019
DOI: 10.1002/cae.22156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of the augmented reality learning environment on electronics laboratory skills of engineering students

Abstract: In engineering education, laboratory experience is powerful in building up the specialized aptitudes and skills of the engineering graduates by structuring and conducting practical experiments. In engineering laboratories, the student often deals with complex laboratory equipment to perform the experiment. Oscilloscope and function generator are frequently used electronic equipment in electronics engineering laboratories. Augmented reality (AR) technology has the capacity to provide a unique learning experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…From recent studies, it has been observed that 3D animated content provides a more immersive experience to the learners. Also with the current change in the pedagogical style of engineering education, learning through games, digital platforms, and modern techniques is more beneficial to the students as it raises students' attention and enthusiasm during the learning activity [32,35]. Augmented reality (AR) has the capability to provide an engaging and interactive learning experience to the students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From recent studies, it has been observed that 3D animated content provides a more immersive experience to the learners. Also with the current change in the pedagogical style of engineering education, learning through games, digital platforms, and modern techniques is more beneficial to the students as it raises students' attention and enthusiasm during the learning activity [32,35]. Augmented reality (AR) has the capability to provide an engaging and interactive learning experience to the students.…”
Section: Introductionmentioning
confidence: 99%
“…through games, digital platforms, and modern techniques is more beneficial to the students as it raises students' attention and enthusiasm during the learning activity [32,35]. Augmented reality (AR) has the capability to provide an engaging and interactive learning experience to the students.…”
mentioning
confidence: 99%
“…One of the engineering innovations developed in AR/VR laboratory of Chitkara University, Punjab, India is AR learning system in which students can work with the virtual replicas of two laboratory equipments that are function generator and oscilloscope. These two equipments are essential for electronics students to observe/display the variation of voltage/current waveforms with respect to time on a two-dimensional plot (Singh et al, 2019). Students can generate different waveforms such as sinusoidal wave, square wave, or triangular wave.…”
Section: Scope Of Enhancement In Practical Skills Of Students During mentioning
confidence: 99%
“…Due to the interesting visualization, interactivity, and game forms of programs based on it, this technology can be used in the development of teaching materials at all levels of education, from preschool to universities. AR allows you to support lectures, seminars, and training with visual materials, show students all aspects of a real object or process being studied, which in general has an enormous effect, improving the quality and pace of educational processes and reducing their cost [8,54].…”
Section: Related Workmentioning
confidence: 99%
“…They allow revealing the students' interest in the subject, stimulate positive emotions, accelerate the process of learning, and help to understand the material better. AR and VR bring the element of a game into the learning process, which certainly positively affects the learners' performance and increase their motivation and confidence [8,11,16,38,54].…”
Section: Introductionmentioning
confidence: 99%